ILMU PENDIDIKAN DALAM WACANA ISLAMISASI ILMU PENGETAHUAN - Junaidi Arsyad; Mayurida Mayurida; Gunawan Gunawan (Pascasarjana UIN Sumatera Utara, 2020)
The idea of Islamization of science has become an interesting phenomenon lately which has always been a hot topic of discussion among Muslim academics. This is interesting because it responds to the development of modern epistemology which is dominated by non-Islamic Western civilization. By using a library research method with a content analysis approach, all information, whether written or printed in the form of a book, will be elaborated on and understood by the contents of the text in order to answer all the research questions. The results of the study indicate that the speed of dissemination of the development of knowledge institutionally is based on the epistemology of Islamic scholarship, which continues to be studied and critically studied. This shows that Islamic teachings are updated on developments and are able to design the future order of life. Even though at the beginning, the conceptual level was more at the epistemological level where science was described as explained by Al-Faruqi, also Kuntowijoyo and M. Amin Abdullah, but contributed greatly to the grand design of Islamic scholarship, especially in Islamic universities..